A case study of secondary school students' disciplinary problems through art therapy / Mas Intaniah Sarimin - Sarimin, Mas Intaniah (2012)
School is the place where students study and enhance themselves with knowledge and moral values. The content of education system in Malaysia was enriched with the development of physical, emotional, spiritual, knowledge and manner. Unfortunately, the content of education cannot make them become a good person in school. Disciplinary problem among school students arise day by day. In urban or rural schools, disciplinary problems become an issue to overcome. The development of technology and gadgets makes this issue getting worse with the increasing number of the physical attacks among school students, fighting, rape, unwed pregnancy, murder and other crime are done by school students. The prevention act from the disciplinary board at schools makes them rebel, so other problems might arise when they start truancy, loitering, bad manners with teacher, vandalism and other disciplinary problem among student especially secondary student. Instead of punishment, counseling approaches were implemented to encourage them to become good person. These approaches of psychological prevention give an opportunity to the researcher to apply art therapy for this group of problematic students in one secondary school in Batu Pahat, Johor by using qualitative mixed media method. Transformation from words to picture hopefully is able to give another perspective to the problematic student to transfer their feeling on the paper why they become trouble makers at school. Then the root of the problems can be dug, the solution can be planned to control the problem among them. This research is conducted to find the reason of disciplinary problem based on disciplinary student and teacher perception and also to find the solution to control this issue. Hopefully this research will give an advantage to the school system to find other opportunity to find the solution toward disciplinary problem among student.